2015
DOI: 10.1016/j.ijid.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcome of Acute Respiratory Infection in Young Children with Underlying Health Condition in Brazil

Abstract: Identification of this high-risk population along with strategies for fast diagnosis might each help to reduce morbidity and mortality in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 30 publications
1
13
2
2
Order By: Relevance
“…Particularly, hRSVs were more frequently detected during autumn (Fisher's exact, P = .004), a pattern already observed in surveillance studies carried out in two distinct São Paulo city hospitals. 22,23 HCoV were more frequently detected during winter (Fisher's exact, P = .011; Figure 1D), as observed previously in a study conducted during 20 years in the United States. 24 The fifth similarity included statistically significant associations of FLU and hRSV infections with more severe symptoms such as fever (Fisher's exact, P = .007 and P = .02, respectively) and of hRSV infections with dyspnea (Fisher's exact, P = .038) ( Figure 1E) Because of coinfections in several patients, the number of individual virus detections (N = 252), including HCoV (N = 34) and hPiV (N = 28), were higher than the number of infected patients.…”
Section: Resultssupporting
confidence: 85%
“…Particularly, hRSVs were more frequently detected during autumn (Fisher's exact, P = .004), a pattern already observed in surveillance studies carried out in two distinct São Paulo city hospitals. 22,23 HCoV were more frequently detected during winter (Fisher's exact, P = .011; Figure 1D), as observed previously in a study conducted during 20 years in the United States. 24 The fifth similarity included statistically significant associations of FLU and hRSV infections with more severe symptoms such as fever (Fisher's exact, P = .007 and P = .02, respectively) and of hRSV infections with dyspnea (Fisher's exact, P = .038) ( Figure 1E) Because of coinfections in several patients, the number of individual virus detections (N = 252), including HCoV (N = 34) and hPiV (N = 28), were higher than the number of infected patients.…”
Section: Resultssupporting
confidence: 85%
“…Previous studies have reported that RSV was the primary cause of SARI in hospitalized children [28][29][30]. In contrast, PIC (34.0%) was the most common pathogen in our sample, although the findings in Beijing and Shanghai differed.…”
Section: Discussioncontrasting
confidence: 81%
“…Given the high co-infection rate in our study, we did not investigate associations between clinical characteristics and individual viral infections. A previous study found that RSV infections were more strongly associated with comorbidities and bronchiolitis than were non-RSV infections [29]. However, it is not clear whether symptoms can be used to identify specific viral infections, and we concluded that no individual symptoms were specific to any viral infection.…”
Section: Discussionmentioning
confidence: 66%
“…Infants with underlying risk factors, particularly those with a history of prematurity or congenital heart disease, are at greater risk for unfavorable sequelae when infected with a respiratory virus (27). In this study, prematurity was found in one patient and co-morbidities were noticed in two patients, including cardiac disorder in one patient (25%) and allergy in the other one (25%).…”
Section: Discussionmentioning
confidence: 62%